(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Cabazitaxel is the newest version of taxanes and is a promising drug for managing various cancers. Like other taxanes, this drug also poses a challenge of solubility and permeability, resulting in a poor oral bioavailability. The present study explores a scalable and economic nanoformulation in the microemulsion form for the oral delivery of cabazitaxel. The developed system substantially improved the drug’s anticancer activity on the breast cancer cell lines and in vivo cancer models. Piperine was also loaded in the microemulsion and it was observed that the incorporation of piperine resulted in an oral formulation with substantially higher oral bioavailability of CBZ vis-à-vis plain drug as well as the microemulsion. The findings infer that biocompatible microemulsions can enhance the oral bioavailability and anticancer activity of CBZ, which was further improved after incorporating piperine.